Assessing the costs and savings of telemedicine: Insights from the consolidated framework for implementation research - Julia Ivanova; Beju Shah; Carrie Foote; Mollie R. Cummins (Digital Health)
Cost reduction is an often-cited reason to use telemedicine. In assessing telemedicine's cost and value, providers often turn to published cost analyses in the scientific literature for guidance. In this commentary on existing telemedicine cost analysis literature, we discuss the generalizability of these analyses and identify the Consolidated Framework for Implementation Research framework to help assess the applicability of a given cost analysis using inner- and outer-setting constructs. Outer-setting factors—location, practice type, and specialty—can substantially affect telemedicine cost and value, as can the implementation setting. While the body of evidence shows telemedicine may often reduce costs, there is still a need for robust cost analyses to guide implementation decisions as telemedicine becomes a mainstay of healthcare provision. Along with a call for more cost research, we ultimately argue that providers should consider a more holistic, value-based approach to determining when and how telemedicine implementation could benefit healthcare delivery.